2017
DOI: 10.1302/2046-3758.610.bjr-2017-0094.r1
|View full text |Cite
|
Sign up to set email alerts
|

How 3D patient-specific instruments improve accuracy of pelvic bone tumour resection in a cadaveric study

Abstract: ObjectivesTo assess the accuracy of patient-specific instruments (PSIs) versus standard manual technique and the precision of computer-assisted planning and PSI-guided osteotomies in pelvic tumour resection.MethodsCT scans were obtained from five female cadaveric pelvises. Five osteotomies were designed using Mimics software: sacroiliac, biplanar supra-acetabular, two parallel iliopubic and ischial. For cases of the left hemipelvis, PSIs were designed to guide standard oscillating saw osteotomies and later man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
0
50
1
Order By: Relevance
“…On the contrary, if the mass is problematic for the PSI, it will be problematic for the cutting whatever the method used. Also, clinical data on pelvis have shown comparable results [ 7 , 30 ]. Third, the sample size was small.…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, if the mass is problematic for the PSI, it will be problematic for the cutting whatever the method used. Also, clinical data on pelvis have shown comparable results [ 7 , 30 ]. Third, the sample size was small.…”
Section: Discussionmentioning
confidence: 93%
“…When the 5 mm acceptability criterion was applied ( 18 Other cadaver studies demonstrated that custom-made jigs improved accuracy in multiple resection planes 16 and provided less cut deviation. 17 Outcomes contrasting computerized navigation and patientspecific guided procedures to the freehand technique have been reported in other orthopaedic subspecialties 23,24 ; however, we believe that our study is the first to compare all three for SI joint tumor resections.…”
Section: Resultsmentioning
confidence: 99%
“…7 Basic science and clinical studies have shown better adherence to predetermined margins as well as other results with the aid of PSI devices. 11,[14][15][16][17][18] The lack of any gold standard cutting method encouraged us to investigate: (1) Does freehand, computerized navigation, or the patientspecific cutting guide technique achieve the most accurate planned cut in a Sawbones model? (2) Which technique causes the least far-side damage to pelvic viscera and important neurovascular structures beyond the resection margins?…”
mentioning
confidence: 99%
“…This reconstruction method is durable but with inherent risks of infection and dislocation. Introduction of computer based navigation and patient specific instrumentation has the potential to increase accuracy of tumor resection and decrease the incidence of implant-specific complications [ [48] , [49] , [50] ]. Poor cancer status, timing, estimated life expectancy and available surgical expertise should be considered in the choice of surgical strategy to optimize the outcome of surgery in these patients.…”
Section: Discussionmentioning
confidence: 99%